A Novel Rectification Efficiency Optimization Method of Receiver for Wireless Power Transfer - Ding, Jianying; Jin, Ke; Xiao, Yiwen; Zhai, Zehao; Zhu, Xirui; Zhou, Weiyang; Li, Xing; Chen, Zhongwei (IEEE transactions on industry applications, 2025)
Microwave wireless power transmission (MWPT) has become a current research hotspot due to its potential to address problems such as power supply in remote areas, short drone flight time, and the lack of non-renewable resources. The microwave receiver plays a crucial role in the MWPT system by receiving RF power and converting it into DC power for use by the load. However, uneven power distribution at the receiver and changes of the output load will lead to mismatch loss and rectification efficiency reduction of the receiver, which greatly limits the application of MWPT. To address the problem, this article proposes a novel method for optimizing receiver of the MWPT system. Firstly, a self-switching rectifier is proposed, which can achieve adaptive rectification without increasing power loss, and has a simple structure and lower cost. Secondly, the power distribution law of the receiver is revealed, and on this basis, an effective power combining strategy is given to improve the power capacity of the receiver and balance the output of each branch. Then, an automatic impedance matcher without adding a microcontroller is presented to achieve automatic impedance matching under a wide output load range. Finally, the correctness and feasibility of this method are verified through experiments.